The Chinese Mind Essentials of Chinese Philosophy and Culture - Moore, Charles A. 1901-1967 (East-West Center Press, 2021)
What are the basic, unique characteristics of the Chinese mind, of the Chinese philosophical tradition, and of the Chinese culture based upon that thought-tradition? Here, in a series of living essays by men of exceptional competence, is an interdisciplinary approach to the essentials of Chinese philosophy and culture.These essays are selected chapters from the Proceedings of the four East-West Philosophers' Conferences held at the University of Hawaii (1939, 1949, 1959, 1964). This volume, published jointly with the University of Hawaii Press, is one in a series of three; the two succeeding volumes will be The Indian Mind and The Japanese Mind. All are intended for the educated reader as well as for the philosophy student and scholar. Though not designed as textbooks, they will provide an excellent base for courses in this area